Caulerpa sertularioides, a green alga spreading aggressively over coral reef communities in Culebra Bay, North Pacific of Costa Rica - Fernández García, Cindy (2005)
Caulerpa sertularioides, is a widespread chlorophyte, that can be confused with C. taxifolia, a highly invasive algae. C. sertularioides has erect, feather-like, occasionally branched fronds; its branchlets are opposite, cylindrical and needle-shaped, with a light green color (Top right) (Littler and Littler 2000). This alga is a new report for Costa Rica’s Pacific coast.